HAK ASASI MANUSIA DAN STATEMENT KEBEBASAN BERAGAMA DALAM AL-QUR’AN: Kajian Tafsir Surat Al-Baqarah Ayat 256 - Wardani, Galuh Retno Setyo; Hidayah, Khoirul; Suwandi, Suwandi (QOF, 2021)
Human right is a concept that is upheld in Islam. His spirit is contained in the Qur'an, one of which discusses religious freedom. This paper was written to answer the question of how is the concept of religious freedom in the interpretation of the Qur'an? This study used maudhu'i method with a linguistic approach. From this search, it was found that the basis of the concept of human rights to guarantee religious freedom is in QS. Al-Baqarah (2): 256. The law that was born from this verse is valid forever. There is no compulsion for other than Muslims to embrace Islam, because the truth is something that should not be forced, even if there are people who do not believe in the truth in Islam, it still will not change the fact that Islam is the true religion. Humans are given the capacity to think and choose with the gift of reason, it is appropriate for humans to determine their own path and be responsible for the consequences of that choice.